Modified Reissner-Nordstrom metric in an external electrostatic field - Halilsoy, M; Al-Badawi, A (Editrice Compositori Bologna, 1998)
We introduce a nem metric that describes a Reissner-Nordstrom black hole coupled to an external, stationary electrostatic field. The field modifies both the horizon and particle geodesics to significant degrees.
Keywords: Electromagnetic-Field; Mass